THE IMPLEMENTATION OF SUMMARIZING ACTIVITY BY USING SOMEBODY WANTED BUT SO (SWBS) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Mursyida Mursyida; Iskandar Abdul Samad; Asnawi Muslem (English Education Journal, 2020)
The aim of this research is to find out if there is a significant difference between the students who were taught through summarizing activity using somebody wanted but so (SWBS) strategy than those who were not taught through the strategy to improve the students’ reading comprehension in terms of finding out the main idea, specific information, word meaning, reference, and inference. This study employed a true experimental design in which there were two classes as the samples classified into experimental and control classes. The classes were chosen by using cluster random sampling and each class consisted of 36 students. In collecting the data, pre-test and post-test were used and the data were analyzed by using SPSS version 21. The result of the study found the post-test mean score at the experimental class is 84.78, and the post-test mean score at the control class is 73.33. Furthermore, the result of the z-score between both experimental and control classes is 6.05 at the level significance of 5% (0.05). Thus, it indicates that there is a significant difference between the students who were taught through SWBS strategy than those who were not taught through this strategy to improve the students’ reading comprehension.